Organized Crime and the Bright Side of Subversion of Law - Astrid Gamba; Giovanni Immordino; Salvatore Piccolo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
When Legislators introduce laws that award amnesties to 'low-rank' criminals co- operating with the justice, top criminals may bribe public officials to subvert the law. Legislators should anticipate this reaction and fight it back by introducing policies that bundle amnesties for low-rank criminals with amnesties to corrupt officials who plea guilty. In fact, the threat of being betrayed by their fellows may induce top-criminals to rely on corruption (to avoid sanctions). However, a suitable amnesty for corrupt officials may increase the conviction risk not only for top-criminal but also for low-rank ones. This domino effect can deter crime more than a policy based only on amnesties to low-rank criminals would: a bright side of subversion of law.
Keywords: K14; K42; D73; D78; 330; Criminal Organizations; Corruption; Leniency